The Population and Transportation Infrastructure of Slovakia during the Second Republic in the years 1938–1939 - Vanek, Peter; Krajčović, Pavol (Études sur la Région Méditerranéenne, 2023)
The main article’s goal is to analyze the impacts of territorial changes dated in 1938 (the Munich Agreement, the Vienna Award, and the Polish territorial claim) on the population and transportation infrastructure of Slovakia. In the area of transportation infrastructure, we focused on four key areas: railways, roads, river and air transportation. According to our own research, we can state that the territorial changes affected the Second Republic viability. As a result thereof, the state lost total 30% of its territory, where approximately onethird of the population lived. In relation to transportation infrastructure, many main routes and roads crossed the new state borders. In this way, the surrounding countries were able to restrict transfer through their territories and thus paralyze inland transportation.